From Curlers to Chainsaws : Women and Their Machines - Walls, Elizabeth MacLeod, 1974-; Cognard-Black, Jennifer, 1969-; Dyer, Joyce; Project Muse. (East Lansing, Michigan : Michigan State University Press, 2016)
The twenty-three distinguished writers included in From Curlers to Chainsaws: Women and Their Machines invite machines into their lives and onto the page. In every room and landscape these writers occupy, gadgets that both stir and stymie may be found: a Singer sewing machine, a stove, a gun, a vibrator, a prosthetic limb, a tractor, a Dodge Dart, a microphone, a smartphone, a stapler, a No. 1 pencil and, of course, a curling iron and a chainsaw. From Curlers to Chainsaws is a groundbreaking collection of lyrical and illuminating essays about the serious, silly, seductive, and sometimes sorrowful relationships between women and their machines. This collection explores in depth objects we sometimes take for granted, focusing not only on their functions but also on their powers to inform identity. For each writer, the device moves beyond the functional to become a symbolic extension of the writer's own mind-altering and deepening each woman's concept of herself.
Mary Quade -- Old Iron: A RestorationMaureen Stanton -- All Flesh Is Grass; Karen Salyer McElmurray -- Driven; Ana Maria Spagna -- More Than Noise; Stage and World; Debra Marquart -- The Microphone Erotic; Elizabeth MacLeod Walls -- I, Phone; Melissa A. Goldthwaite -- Body, Camera, Self; Diana Salman -- Lebanese Airwaves; Monica Berlin -- Remembered Is Misremembered, Then Turns; The Writer's Studio; Jen Hirt -- Swingline Nine; Sue William Silverman -- The Qwertyist; Karen Outen -- On Typing and Salvation; Nikky Finney -- Inquisitor and Insurgent: Black Woman with Pencil, Sharpened; Contributors.
English.
Description based on print version record.
Keywords: Tools -- Social aspects; Technology and women; Material culture; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Women's Studies; material culture (discipline); Culture materielle; Femmes et technologie; Implements, utensils, etc. -- Social aspects; Tools -- Social aspects; Material culture; Technology and women; Electronic books